Changes in postural control with aging and Parkinson's disease. - Romero, D.H (IEEE Engineering in medicine and biology magazine)
Deterioration of the neural mechanisms that govern postural stability and other mechanisms can disrupt the balance system. This article briefly outlines the research on postural control in elderly adults and patients with Parkinson's disease (PD). Parkinson's disease may be considered a form of accelerated aging, and as such, many of the abnormal postural control characteristics found in the elderly are observed and magnified in PD patients. The symptoms contributing to impaired postural control include the amplitude of body sway, delayed sensory and response processing, as well as prolonged, reduced, and inflexible responses to perturbations. In general, the research suggests that although aging and PD contribute to changes in postural control, some symptoms are not inherent to age or disease but can be modified through the health and physical fitness of the person.